The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12879-018-3448-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, organ failure, inflammatory markers and prediction of mortality in patients with community acquired bloodstream infection

Abstract: BackgroundCommunity acquired bloodstream infection (CABSI) in low- and middle income countries is associated with a high mortality. This study describes the clinical manifestations, laboratory findings and correlation of SOFA and qSOFA with mortality in patients with CABSI in northern Vietnam.MethodsThis was a retrospective study of 393 patients with at least one positive blood culture with not more than one bacterium taken within 48 h of hospitalisation. Clinical characteristic and laboratory results from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…Furthermore, cerebral failure, as in our study, had the strongest association with short-term mortality, followed by respiratory and circulatory failure, the latter in contrast to our study, and hepatic and cerebral failure were associated with long-term mortality 14. In organ failure patients with positive blood culture, the highest in-hospital mortality was observed in patients with circulatory failure followed by respiratory and cerebral 15. At the ICU, the in-hospital mortality is described around 35% and 1-year mortality around 45%7 13 which is higher than our findings, and in contrast to our numbers, hepatic failure is described with highest short-term risk of death, but in accordance with our study respiratory has the lowest short-term mortality 6 13.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, cerebral failure, as in our study, had the strongest association with short-term mortality, followed by respiratory and circulatory failure, the latter in contrast to our study, and hepatic and cerebral failure were associated with long-term mortality 14. In organ failure patients with positive blood culture, the highest in-hospital mortality was observed in patients with circulatory failure followed by respiratory and cerebral 15. At the ICU, the in-hospital mortality is described around 35% and 1-year mortality around 45%7 13 which is higher than our findings, and in contrast to our numbers, hepatic failure is described with highest short-term risk of death, but in accordance with our study respiratory has the lowest short-term mortality 6 13.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, organ failure affects not only in-hospital prognosis but also long-term morbidity and mortality 12–14. In addition, different prevalences are described for different organ failures, and the mortality varies by organ failure and number of organ failures 15–17. These studies are less useful for the public health planning as well as upfront clinical evaluations and decisions, because patients included are selected, and might be considerable different from the very diverse acutely ill patients identified and treated upon arrival to the ED.…”
Section: Introductionmentioning
confidence: 99%
“…Multiorgan dysfunction is common in patients with BSI. It was reported that the SOFA performed well in predicting organ dysfunction in some patients with BSI (24). However, no previous study has considered the SOFA score in patients with PBSI.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, we also evaluated some prognostic systems, which have been reported link with mortality of patients with BSI (24,25). We found that the SOFA ,APACHE II and SAPS II all had good predictive accuracy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream infection (BSI) is associated with a high risk of mortality ( 1 3 ). This is especially true in critically ill patients, in whom BSI has reported mortality rates of 30–47% ( 4 7 ). Clinical signs and symptoms of BSI are nonspecific, and published guidelines do not provide clear indications for when it is most appropriate to obtain blood cultures ( 8 ).…”
mentioning
confidence: 99%